Impacts of PM on Indoor Air Quality of Airport Terminal Buildings in a Core City of North China Plain - Yunting Zhao; Wenhui Zheng; Simeng Ma; Weikai Kong; Bo Han; Jian Yu (Aerosol and Air Quality Research)
Abstract With the economic growth and globalization, a great deal of airports are being or planned to be constructed or retrofitted in China. The air quality in airport terminal buildings has not been studied as in-depth as airport ambient air quality. Due to its unique architectural and operational characteristics, the airport terminal buildings have individual performance of indoor air quality. The contribution of outdoor particulate matter (PM) to indoor environment and passengers’ exposure to indoor PM is not well understood. The indoor (i.e., terminal buildings) and outdoor PM concentrations with particle sizes from 0.25 to 32 µm of Tianjin Binhai International Airport (IATA: TSN) were monitored continuously during two cases in winter and summer 2020. Higher indoor PM concentrations occurred in winter as well as in the arrival halls of TSN. During winter case, the indoor sources contributed more to the indoor environment than the outdoor sources, whereas the opposite was found during summer case. Sharp variation of indoor PM number concentrations existed in particles within the range of 0.25–0.40 µm in size, with a peak number concentration at particle size of about 0.30 µm. PM with smaller particle sizes were more likely to enter the indoor environment from outdoor. The comprehensive exposure in the TSN terminal buildings was higher than those in the transportation microenvironments, residences and other buildings. Significant diurnal variations of Respiratory deposition dose (RDD) were observed under various exposure durations. Our results highlight the need for further monitoring and improving the air quality in the terminal buildings.